Aldehyde dehydrogenase 2*2 knock-in mice show increased reactive oxygen species production in response to cisplatin treatment - Kim, Jeewon (J Biomed Sci, 2017)
BACKGROUND: The aldehyde dehydrogenase (ALDH) enzyme family metabolizes and detoxifies both exogenous and endogenous aldehydes. Since chemotherapeutic agents, such as cisplatin, generate cytotoxic aldehydes and oxidative stress, and chemoresistant cancer cells express high levels of ALDH enzymes, we hypothesized that different ALDH expression within cells may show different chemosensitivity. ALDH2 has the lowest Km for acetaldehyde among ALDH isozymes and detoxifies acetaldehydes in addition to other reactive aldehydes, such as 4-hydroxy-nonenal, malondialdehyde and acrolein produced from lipid peroxidation by reactive oxygen species (ROS). Thus, cells with an ALDH2 variant may sensitize them to these ROS-inducing chemotherapy drugs. METHODS: Here, we used wild type C57BL/6 mice and ALDH2*2 knock-in mutant mice and compared the basal level of ROS in different tissues. Then, we treated the mice with cisplatin, isolated cells from organs and fractionated them into lysates containing mitochondrial and cytosolic fractions, treated with cisplatin again in vitro, and compared the level of ROS generated. RESULTS: We show that overall ROS production increases with cisplatin treatment in cells with ALDH2 mutation. The treatment of cisplatin in the wild type mice did not change the level of ROS compared to PBS treated controls. In contrast, ALDH2*2 knock-in mutant mice showed a significantly increased level of ROS compared to wild type mice in tongue, lung, kidney and brain tissues without any treatment. ALDH2*2 mutant mice showed 20% of the ALDH2 activity in the kidney compared to wild type mice. Treatment of ALDH2*2 mutant mice with cisplatin showed increased ROS levels in the mitochondrial fraction of kidney. In the cytosolic fraction, treatment of mutant mice with cisplatin increased ROS levels in lung and brain compared to PBS treated controls. Furthermore, ALDH2*2 mutant mice treated with cisplatin showed increased cytotoxicity in the kidney cells compared to PBS treated mutant controls. CONCLUSIONS: These data indicate that deficiency in ALDH2 activity may contribute to increased cisplatin sensitivity and cytotoxicity by producing more ROS by the treatment. Based on these data, the amount of cisplatin used in patients may need to be adjusted based on their ALDH2 variant profile.